La enseñanza del ajedrez como herramienta didáctica en el desarrollo de la capacidad de cálculo en niños de cuarto grado, Loja, 2023. - Cuenca Patiño, Byron Michael (2023)
The purpose of the Curricular Integration Work is to use chess as a didactic tool to enhance learning and offer alternative educational approaches to fourth-grade students at Pío Jaramillo Alvarado high school. A qualitative study was conducted, which collected data from practical experimentation, an interview with the grade teacher, and subsequent analyses based on parameters determined by the National Education System and related literature. The expert panel technique was used to plan the project, and a course at the institution served as a sample for the methodological proposal. The proposal involved using chess to achieve specific objectives and obtain benefits in the teaching and learning process. Two chess sessions were conducted each week, each lasting one hour, in line with the proposal's planning. The academic performance of fourth-grade students in Mathematics was assessed in the academic year 2022 and 2023 to determine whether there was progress in academic performance through chess practice. The analysis showed an improvement of 0.70 tenth between grades from different partials, demonstrating the effectiveness of the research plan. The autonomy and reasoning demonstrated by each student were instrumental in achieving this improvement. In conclusion, the proposal was a significant contribution to the institution's education system, offering students a new way of learning while improving their academic performance. Keywords: chees, academic performance, didactic games, methodology, education.